Separation and Characterization of Potato Lipid Acylhydrolases - Hasson, Edna P. (1976)
Three distinct potato (Solanum tuberosum) lipid acyl-hydrolases have been isolated and characterized. Nonfluorescent esters of the fluorescent alcohols, N-methylindoxyl and N-methylumbelliferone, have been used as convenient substrates for lipid acyl-hydrolase estimation. Enzyme I has been shown to be a neutral lipase which favors glyceryl triolein over the di- and monoolein, which shows no activity with phospho- and galactolipids and which favors long chain fatty acid esters of N-methylindoxyl over the butyrate ester. Enzyme II, while attacking glyceryl mono- and diolein, as well as favoring the butyrate ester of N-methylindoxyl over the myristate ester, is basically a phospholipid and galactolipid acyl-hydrolase. Enzyme III may reasonably be considered an esterase, since it hydrolyzes glyceryl monoolein exclusively among the neutral lipids, shows minimal activity on phospho- and galactolipids, and hydrolyzes N-methylindoxylbutyrate exclusively compared with N-methylindoxyl-myristate.